The effect of heat stress on clinicopathological changes and immunolocalization of antigens in experimental Streptococcus agalactiae infection in Red hybrid tilapia (Oreochromis spp.) - Omar, Noraini; Abdul Rashid, Jahwarhar Nazrin; Mohd Yusoff, Md Sabri; Emikpe, Benjamin Obukowho; Tanko, Polycarp Nwunuji; Hassan, Latiffah; Salleh, Jamil (Veterinary World, 2013)
Aim: To understand the influence of environmental temperature on streptococcosis, heat stress associated pathological changes in acute streptococcosis in red tilapia using various routes of infection was investigated. Materials and Methods: Red hybrid tilapia were inoculated with 109 CFU/ml of agalactiae using intraperitoneal (IP), immersion (IM), and immersion cut (IC) which were maintained at 34C for 24 hours while the positive control groups were infected using similar routes but maintained at 28C and the negative control was at 34C without infection. Samples from the gills, brain, eyes and kidney were taken for bacterial isolation, polymerase chain reaction (PCR), histopathology and immunohistochemistry (IHC). Results: Diseased fish showed skin haemorrhage, fin haemorrhage and exophthalmia with more signs in IP route of infection followed by IC and lastly IM at 34C. The bacteria were isolated and detected with PCR in all the organs of fish from 4 hour post-challenge (hpc). The lesions were noticed earlier and severe in heat stressed groups from 4 hpc with 50% mortality in IP group while for all, the bacterium was isolated from 4 hpc in the brain. IHC test also detected the antigen in the tissues as early as 4 hpc with intense staining in the heat stressed group, IP followed by IC and IM routes. Positive immunostaining were observed in the thrombi, meningeal vessels, choroid and interstitial haemorrhagic areas. Conclusion: The severe lesions observed in the brain, eye and kidney under heat stress reveals its contributory role to the mortality pattern and severe pathological changes associated with streptococcosis in fish.